The Politicization of Heresy: Foucault's Analysis of the Hamzah Fansuri and Nuruddin Ar-Raniry Debate - Wahab, Hamzah Abdul (POLITEA, 2023)
This article delves into the historical debates between two prominent figures, Hamzah Fansuri, and Nuruddin Arraniry, in the context of Islamic civilization in Aceh. While existing literature recognizes this significant event as the genesis of enduring Islamic thought in Aceh, a crucial aspect remains underexplored - the analysis through the lens of power/knowledge theory by Michel Foucault. Consequently, this article aims to fill this scholarly gap by employing a political knowledge approach to reexamine the conflict between these two intellectuals. By focusing on the motives of power in Nuruddin Arraniry's accusations of heresy against Hamzah Fansuri and considering the prevailing political landscape, the article argues that the charges were primarily driven by a quest for influence within the Aceh sultanate. This perspective leads to the conclusion that the knowledge conflict between Hamzah Fansuri and Nuruddin Arraniry stemmed from the underlying tension between Sufism and fiqh, calling for a reevaluation of their ideological divergence.